THE FEATURES OT THE INTERRELATIONSHIP BETWEEN THE ATTITUDE TO THE OWN BODY AND SELF-ATTITUDE OF DIFFERENT AGED WOMEN - Фещенко, Катерина Андріївна; Луценко, Олена Львівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article considers the problem of the relationship between the attitude to the own body and self-attitude of different aged women. Self-attitude is a phenomenon that reflects a general positive or negative attitude to own personality. Many scientists such as Z. Freud, A. Adler, O.O. Skugarevsky, S.V. Sivukha emphasized the importance of the body in forming a person’s mental characteristics. Attitude to the own body is formed in the process of socialization through social institutions, art, science, everyday experience. In this research there was studied the relationship between the attitude to the own body and self-attitude of different aged women. Sample included women of two age groups: 20-40, 41-60. It was found out that dissatisfaction with own body in both groups was not expressed. We revealed that self-esteem of functional (endurance, strength, flexibility, speed, agility), anatomical (face, figure, legs, hands) and social (clothing, accessories, and cosmetics) characteristics of their bodies are on the high levels in both groups. Women between 41 and 60 have more interconnections between attitude to their bodies and different aspects of self-attitude (self-esteem, self-accusation, self-sympathy, etc.) in comparison with women of 20-40 ages. Middle-aged women tend to have higher self-acceptance and self-esteem than the younger group. From an evolutionary perspective, women are interested in being attractive to men. It increases their chances of getting a healthy partner who will provide them with the resources they need to raise their children. Studies show that men unconsciously pay attention to body proportions, skin quality and other health indicators. In our opinion, social characteristics have evolutionary importance. Social characteristics correlate with the expected attitudes of others in group of middle-aged women. Artificial appearance enhancement is aimed at attracting men and scaring away potential rivals. Perhaps women initially attract the opposite sex due to anatomical features, and when their body starts to change, they pay more attention to social ones.